Performance of Combined Water Turbine with Semielliptic Section of the Savonius Rotor - Kaprawi Sahim; Dyos Santoso; Agus Radentan (International Journal of Rotating Machinery)
The Darrieus turbine is a suitable power generation in free stream flow because it is simple in construction, but it has the disadvantage of its small starting torque. The Savonius turbine has a high starting torque but the efficiency is smaller than that of Darrieus turbine. To improve the starting torque of Darrieus turbine, the Savonius buckets are introduced into the Darrieus turbine and the combined turbine is called Darrieus-Savonius turbine. In this study, three semielliptic sections of aspect ratio 0.8 were used for Savonius bucket while the Darrieus blade used three wings of airfoil NACA 0015. The Darrieus-Savonius turbine’s performances were studied experimentally in an irrigation canal of South Sumatera, Indonesia. The results show that the distance of Savonius buckets from the shaft centre influences performance of combined turbine, and the attachment angle of Savonius rotor made important variation of turbine performance.